The contribution of EU funds in investments of the Independent Public Health Care Unit in Kraśnik - Kos, Marek; Książek, Piotr; Drop, Bartłomiej (Polish Journal of Public Health, 2012)
Poland’s accession to the EU has opened unique opportunities for the development of our macroregion. The opportunities are created by, inter alia, the Structural Funds that balance the gap between different regions. In the whole country a significant number of operational programs providing financial support for the most important social problems of the regions have been implemented. Some of them concern a specific area dealing with health and social policy.The authors present the relevance of targeting structural funds in the health care area on the example of poviat healthcare unit, namely Independent Public Health Care Unit in Krasnik (SPZOZ Kraśnik). A few years ago this unit had the old, worn-out hospital buildings and depleted medical equipment. With several EU projects implemented under the Integrated Regional Operational Programme, Infrastructure and Environment Operational Programme, the Regional Operational Programme of Lubelskie Province and the Lublin Foundation EKOFUNDUSZ, it acquired funds for the implementation of such tasks as thermal modernization of hospital buildings, reconstruction of the operating theater and specialist outpatient clinics, purchase of modern, medical specialized equipment, computerization of the unit and the implementation of the new information technologies (among others, e-health services). These actions resulted in nearly 18 million PLN obtained from the EU funds and the total amount of the investments held in this period was more than 25 million PLN. At present it is difficult to imagine SPZOZ Kraśnik without these necessary investments. Great involvement in these activities of the Poviat Starosty in Kraśnik should be noted here. Kraśnicki Poviat, as the founding body of SPZOZ in Kraśnik has allocated nearly 7.8 million PLN for investments co-financed by the EU funds as so called “own contribution” and constantly supervised the work in this field. At present, it can be seen that the lack of financial support from the European Union funds could result in lower level of provided health services, and even the elimination of health care units.